Organic banana 2000: Towards an organic initiative in the Caribbean - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 2001)
Organic banana 2000: Towards an organic initiative in the Caribbean Report of the international workshop on the production and marketing of organic bananas by smallholder farmers. 31 October 4 November 1999, Santo Domingo, Dominican Republic.